Association of nutritional status, protein and iron intake, and physical activity with hemoglobin levels in adolescent girls: a case-control study in Rural East Java, Indonesia: 10.55131/jphd/2025/230309 - Kartika Pibriyanti; Indarto, Dono; Auliya Qudsi, Desy; Lulu’ Luthfiya; Fajr Rooiqoh, Qothrunnadaa; Mufidah, Indahtul; Amala, Nur; mayupinasti, Ladya; Claresta, Ivena (Journal of Public Health and Development, 2025)
Anemia among adolescent girls is a significant public health concern, negatively affecting physical development, cognitive function, and quality of life. This study aims to analyze the impact of nutritional status, dietary intake, and physical activity on hemoglobin levels. A case-control study design was employed on 116 adolescent girls aged 12-18 years. Data were collected through structured interviews. Statistical tests were used to determine the association between nutritional status, protein and iron intake, and physical activity with hemoglobin levels. Adolescent girls with good nutritional status had a significantly lower risk of anemia compared to those with poor nutritional status (p < 0.05). Low protein intake, both in quantity and frequency, increased the risk of anemia nearly sixfold (OR = 5.884, 95% CI = 2.634–13.146; p < 0.05). This finding underscores the critical role of sufficient protein intake in supporting hemoglobin synthesis and preventing anemia. Adequate consumption of iron-rich foods was significantly associated with higher hemoglobin levels. Regular physical activity was also found to have a protective effect, with physically active adolescent girls demonstrating better hemoglobin levels than their less active counterparts. This suggests that an active lifestyle not only improves circulation and red blood cell production but also helps maintain optimal hemoglobin levels. In conclusion, good nutritional status, sufficient protein and iron intake, and regular physical activity are key factors in preventing anemia among adolescent girls. These findings emphasize the importance of holistic nutritional interventions, including improved dietary quality and promotion of physical activity, to reduce anemia prevalence.